DIGITAL TRANSFORMATION OF ECONOMIC NETWORKS: ENERGY AND LOGISTICS ("Conference on Universal Science Research 2023", 2024)
This article explores the profound impact of digital transformation on economic networks, specifically within the energy and logistics sectors. It examines how digital technologies such as IoT, AI, and blockchain are reshaping operations, optimizing efficiencies, and driving innovation. The study underscores the implications for stakeholders, from businesses to policymakers, highlighting opportunities and challenges in this evolving landscape.